Acceptance level of online coaching- a qualitative study on online entrepreneurship ideation classes; case study of a private university - Muhammad Ali Rahman (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
As the pandemic hits, all aspects in our life had to adjust, including the education sector. Entrepreneurship education also had to adapt with such condition by having its online sessions. This study investigates the acceptance level of the students in online coaching sessions. The study was taking place in a private university in Jakarta, Indonesia, and mainly focusing on how the students of entrepreneurship ideation classes respond within their online classes. Three findings were found in this research; the varies acceptance level of the students; the broad type of business ideas; and the lecturers different approach on delivering the ideation concepts.